Systematics of the Euro-Mediterranean Empis (Kritempis) (Diptera: Empididae: Empidinae) - Daugeron, Christophe (Zootaxa, 2009)
The Euro-Mediterranean subgenus Kritempis Collin of Empis Linnaeus is here redefined on the basis of three synapomorphies, namely (1) hypandrium reduced to its lateral arms, (2) presence of a posteroventral group of spine-like setae on the female mid tibia at base, (3) anal vein faint, incomplete. This subgenus includes eight species: Empis (K.) algira Macquart, E. (K.) livida Linnaeus, E. (K.) macquarti Becker, E. (K.) macropalpa Egger, E. (K.) nigrimana Becker, E. (K.) sardoa sp. nov., E. (K.) sibillina Bezzi and E. (K.) taffertensis sp. nov. A detailed diagnosis of the group as well as a key to all known species is provided. All species are described or redescribed, exclusive of the well-known E. (K.) livida. The holotype of E. (K.) algira is identified and a lectotype designated for E. (K.) macquarti, E. (K.) macropalpa and E. (K.) sibillina. Empis hoffmannseggii Loew is moved from the subgenus Kritempis to the subgenus Coptophlebia Bezzi. The subgenus is restricted to the Mediterranean basin exclusive of E. (K.) livida which is widely distributed in Europe and Algeria where the species is newly recorded.